Changes in Gene Expression in Leaves of Cacao Genotypes Resistant and Susceptible to Phytophthora palmivora Infection - Baruah, Indrani K.; Ali, Shahin S.; Shao, Jonathan; Lary, David; Bailey, Bryan A. (Frontiers in Plant Science, 2022)
Black pod rot, caused by Phytophthora palmivora, is a devastating disease of Theobroma cacao L. (cacao) leading to huge losses for farmers and limiting chocolate industry supplies. To understand resistance responses of cacao leaves to Phytophthora palmivora, stage 2 leaves of clones ICS1, CCN51, and Pound7 were inoculated with zoospores and monitored for symptoms out to 48 hours. Pound7 consistently showed less necrosis than ICS1 and CCN51 48 h after inoculation. RNA-Seq was carried out on samples 24 h post inoculation. A total of 24,672 expressed cacao genes were identified and 2521 transcripts showed induction in at least one Phytophthora palmivora treated clone compared to controls. There were 115 genes induced in the Phytophthora palmivora treated samples in all 3 clones. Many of the differentially expressed genes were components of KEGG pathways important in plant defense against pathogens: Plant MAPK signaling pathway, Plant hormone signal transduction, Phenylpropanoid biosynthesis, Plant pathogen interactions, α-Linolenic acid metabolism, Ethylene biosynthesis, and Terpenoid backbone biosynthesis. We further analyzed the cacao leaf transcriptome in detail focusing on gene families encoding proteins important in plant defense: Germin-like, WRKY transcription factors, Ubiquitin-associated, Lectin-related, Pathogenesis-related, Glutathione-S-Transferases, and proteases. A search of putative cacao resistance genes within the cacao transcriptome identified 89 genes with prominent LRR domains, 170 protein kinases encoding genes, 210 genes with prominent NB-ARC domains, 305 lectin-related, and 97 cysteine-rich RK. There was a massive re-programming defense gene processes in susceptible cacao leaf tissue after infection which was restricted in the resistant clone Pound7. Most genes induced in Pound7 were induced in ICS1/CCN51. The level of induction was not always proportional to infection level raising the possibility that genes are responding to infection more strongly in Pound7. There were also defense-associated genes constitutively deferentially expressed at higher levels in specific clones possibly providing a prepositioned defense. Many of the defense genes occur in blocks where members are constitutively expressed at different levels and some members are induced by Ppal infection. With further study, the identified candidate genes may be useful as markers for breeding disease resistant cacao clones against Phytophthora palmivora.